TARGET COSTING DALAM EFISIENSI PERENCANAAN BIAYA PRODUKSI UMKM BATIK BANYUWANGI - Ammar, Zhafran (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2024)
This research was carried out using quantitative data analysis methods. This research describes an explanation of matters related to the application of the target costing method to UMKM Mysoen Batik Banyuwangi with data obtained by researchers. The data used in the research uses primary data by conducting interviews, observations and documentation at the research location. Target costing can make production costs at UMKM Mysoen Batik Banyuwangi more efficient. This target costing method can minimize production costs. The profit earned by UMKM before implementing target costing was IDR 8,284,000.00 or 18.6% of total product sales. After implementing target costing, UMKM can produce an expected profit of IDR 11,759,000.00 or around 26%. The target costing method is efficient if used, because it can make it easier for a company to reduce production costs, UMKM can achieve cost savings of 9.6% with cost savings of IDR 3,475,000.00